Konsep Maqasid Syariah Jasser Auda Melalui Pendekatan Sistem - Muhammad Mattori; Rusdiana (SETYAKI : Jurnal Studi Keagamaan Islam, 2023)
Jasser Auda tries to contribute his thoughts to answer current Islamic legal problems using the Maqasid Syariah discipline. Maqashid Syariah which is familiar in Islamic society today is known as Dharuriyah, Hajiyyat, and Tahsiniyyah as well as the concept of Dharuriyatul Khamsah or maintaining the five basic principles of human life, namely; hifdz ad-diin (Maintenance of Religion), hifdz al-nafs (Maintenance of the Soul), hifdz al-aql (Maintenance of Intellect), hifdz al-nasl (Care of Offspring), and hifdz al-maal (Maintenance of Property). However, in this case Jasser Auda brings a new concept to the Maqasid Syariah discipline by utilizing a systems approach. In his book entitled Maqasid Sharia as Legal Philosophy: A Systems Approach which contains Jasser Auda's thoughts regarding the systems approach in Maqasid Sharia, it can be said that it is difficult to understand, because it is presented in very standard and scientific language. Therefore, this article tries to make it easier to understand Jasser Auda's concept of Maqasid Syariah before studying it further in the main book. This research method uses qualitative methods and is a type of library research. The research results show that Jasser Auda has formulated six systems approaches in playing the role of maqasid sharia in understanding the Qur'an and hadith, as well as a framework of thinking in the discipline of ushul fiqh, namely; Cognition System (Cognitions), Holistic (Holism), Openness (Openness), Hierarchy-Interrelation, Multidimensional (Multi-Diminsions), Purposeful (Purposfulness). And what was conceptualized by Jasser Auda did not necessarily abandon the methods of previous scholars or the concepts of maqasid sharia initiated by previous scholars, but was still used as material for study and used to realize the purposes of Islamic law.